Geometric construction of generalized cubic splines - Paolo Costantini (Rendiconti di Matematica e delle Sue Applicazioni, 2006)
We study the Bézier-like, geometric properties of four dimensional spaces of the form span < u_k, P_1, v_k >, where u_k and v_k are subject to general conditions, and describe the geometric construction of the corresponding spline spaces.